Advances in Global Marketing A Research Anthology (Springer International Publishing, 2018)
This book of expert contributions provides a comprehensive analysis of contemporary global marketing issues under different international business settings. It covers a wide array of key areas of international marketing research such as cross-cultural consumer behavior, foreign market entry modes, international entrepreneurship, international marketing strategy, country-of-origin effects, internationalization process, international buyer-seller relationships, corporate social responsibility, and international marketing performance. With both theoretical and empirical contributions by prominent researchers from all over the world, the book highlights and advances extant knowledge on global marketing and offers recommendations for future research. It builds a useful reference for scholars, doctoral researchers, and senior students in international marketing/business. .